Hudud still a stumbling block - Ariff, Syed Umar; Lai, Adrian (New Straits Times, 2015)
KUALA LUMPUR: How well will Gerakan Harapan Barn (GHB) fare in the new opposition pact, with hudud remaining part and parcel of the Pas splinter group's core ideology?